Mengenal Hukum Udhiyah dan Adab Berkurban dalam Islam - Oktavia Rahmadani; Ratna Sholihah; Aisyah Hana Robbani; Mahmud Alfayed; Roza Andini; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The act of sacrifice (udhiyah) is a form of worship in Islam that holds profound spiritual and social values. Sacrifice aims to draw closer to Allah SWT while demonstrating solidarity with others through the distribution of meat to the community, especially those in need. However, the implementation of sacrifice is often not fully understood, particularly regarding its rulings and etiquettes, such as the selection of animals, slaughtering procedures, and meat distribution. This study aims to provide a comprehensive understanding of the rulings of udhiyah and the etiquettes of sacrifice based on Islamic law.The research employs a qualitative approach with a library research method. Data were collected from primary sources such as the Qur'an and hadith, as well as secondary sources including books of Islamic jurisprudence, scholarly journals, and other relevant literature. Data analysis was conducted descriptively to identify and organize systematic insights related to the topic.The results indicate that sacrifice is obligatory for those who can afford it according to some scholars, while the majority consider it a strongly recommended act (sunnah muakkad). The etiquettes of sacrifice include sincere intentions, selecting animals that meet Islamic requirements, proper and humane slaughtering, and proportional meat distribution. Sacrifice also holds spiritual wisdom, such as strengthening faith and gratitude, as well as social benefits by fostering community bonds through sharing.This study concludes that sacrifice is not merely an annual ritual but also a reflection of values such as devotion, sincerity, and solidarity that must be instilled continuously in the lives of Muslims.